Internet addiction and mental health: a cross-sectional study and mediation analysis in medical students with a psychiatric major - Lu, Ying; Lu, Yue; Tian, Yu; Gan, Yu; Chen, Xiaolu; Li, Xiao (Frontiers in Psychiatry, 2025)
BackgroundInternet Addiction (IA) has become a significant public health issue, particularly among medical students. However, research on IA within medical students with a psychiatric major, who receive specialized mental health training, remains limited. This study aimed to examine the prevalence of IA and its associations with mental health variables (depression, anxiety, impulsivity) and social factors among medical students with a psychiatric major, while exploring the mediating role of mental health variables in the relationship between academic year and IA.MethodsA cross-sectional survey was conducted with 390 medical students with a psychiatric major at Chongqing Medical University from February to May 2021. Participants completed validated instruments, including Young’s Internet Addiction Test (Y-IAT), Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and Barratt Impulsiveness Scale (BIS-11). Demographic and social factors were analyzed using Mann-Whitney U tests, chi-square test, correlation analyses. Mediation analyses were conducted using the SPSS PROCESS macro (Model 4).ResultsThe average Y-IAT score was 37.57 ± 13.80, with 17.7% meeting the criteria for IA (Y-IAT ≥50). Additionally, participants reported low levels of depressive (PHQ-9 = 2.04 ± 3.01) and anxiety symptoms (GAD-7 = 1.26 ± 2.58). IA was significantly associated with increased impulsivity (r = 0.534, p < 0.001), depression (r = 0.399, p < 0.001), anxiety (r = 0.347, p < 0.001), academic stress (r = 0.239, p < 0.001), poor peer relationships (r = 0.199, p < 0.001), and peer bullying experiences (r = 0.137, p < 0.05). A higher academic year was associated with a reduction in IA, partly mediated by decreased impulsivity (B = −0.7556, 36.60%) and depressive symptoms (B = −0.2640, 12.80%).ConclusionMedical students with a psychiatric major showed a relatively lower prevalence of IA, depressive and anxiety symptoms. Higher academic years were associated with reduced IA via lower impulsivity and depressive symptoms, potentially due to enhanced psychological literacy. Additionally, poor peer and parental relationships, along with experiences of peer bullying, were linked to higher IA risk, highlighting the importance of stronger social support and early intervention. Future studies should explore targeted psychological and educational interventions to mitigate IA among students.